Réponses

2014-10-23T23:21:42+02:00
(2x-6)(4-6x)+(7x+1)(x-3)
2(x-3)(4-6x)+(7x+1)(x-3)
(X-3)[2(4-6x)+(7x+1)]
(X-3)(8-12x+7x+1)
(X-3)(-5x+9)

(2x-5)^2+3x(4x-10)
(2x-5)^2+3x*2(2x-5)
(2x-5)[2x-5+6x)
(2x-5)(8x-5)
  • Utilisateur Brainly
2014-10-23T23:23:38+02:00


6. A = (2x - 6) * (4 - 6x) + (7x + 1) * (x -3)

A = 2 * (x-3) * (4- 6x) + (7x + 1) * (x-3)

A = (x - 3) * [2 * (4 -6x) + (7x + 1)]

A = (x - 3) * [(8 - 12x) + 7x + 1)]

A = (x - 3) * (8 - 12x + 7x + 1)

A = (x - 3) * (9 - 5x)


7. A = (2x - 5)² + 3x * (4x - 10)

A = (2x - 5) * (2x - 5) + 3x * 2 * ( 2x - 5)

A = (2x - 5) * [(2x-5) + 3x *2]

A = (2x - 5) * (2x - 5 + 6x)

A = (2x - 5) (8x - 5)